Transcatheter mitral valve replacement to treat rheumatic mitral stenosis: a case series - Ping Jin; Hong Guo; Yu Mao; Mengen Zhai; Yang Liu; Jian Yang (Frontiers in Cardiovascular Medicine)
BackgroundRheumatic mitral stenosis (RMS) is a common valvular heart disease in developing countries. We sought to evaluate the early experience of patients with RMS undergoing transcatheter mitral valve replacement (TMVR).MethodsIn this retrospective study, a total of 5 RMS patients accepted TMVR. All patients underwent computed tomography and echocardiography before having the procedure. After the preprocedural comprehensive evaluations, the surgeons planned to use the Prizvalve (a novel balloon-expandable transcatheter aortic valve system which is now under the clinical registration study) for TMVR. Clinical data were collected at baseline, before discharge, and at the 30-day follow-up.ResultsThe median age of the 5 RMS patients was 61 years (range 60–77 years); 60% were male, and the median Society of Thoracic Surgeons score was 13.3% (range 6.2–17.1%). TMVR was successful in all patients. Postoperative transesophageal echocardiography showed that 60.0% (n = 3) of the patients had no paravalvular leakage and 40.0% (n = 2) had trace paravalvular leakage. The median postoperative peak velocity decreased to 1.4 m/s (range 1.1–1.7 m/s), and the median pressure gradient decreased to 3 mmHg (range 2–3 mmHg). No deaths occurred at the 30-day follow-up, and all patients had an improvement of ≥1 on the New York Heart Association functional rating.ConclusionsOur early experience with TMVR in RMS patients suggests that it is a safe and feasible procedure. The early results of the procedure are acceptable and provide bright prospects and directions for the precision treatment of RMS. Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT02917980).